Application of emerging technologies to obtain legume protein isolates with improved techno‐functional properties and health effects. Issue 3 (26th March 2022) - Bou, Ricard; Navarro‐Vozmediano, Paola; Domínguez, Rubén; López‐Gómez, Miguel; Pinent, Montserrat; Ribas‐Agustí, Albert; Benedito, José J.; Lorenzo, José M.; Terra, Ximena; García‐Pérez, José V.; Pateiro, Mirian; Herrera‐Cervera, José A.; et al.
Abstract: Current demand of consumers for healthy and sustainable food products has led the industry to search for different sources of plant protein isolates and concentrates. Legumes represent an excellent nonanimal protein source with high‐protein content. Legume species are distributed in a wide range of ecological conditions, including regions with drought conditions, making them a sustainable crop in a context of global warming. However, their use as human food is limited by the presence of antinutritional factors, such as protease inhibitors, lectins, phytates, and alkaloids, which have adverse nutritional effects. Antitechnological factors, such as fiber, tannins, and lipids, can affect the purity and protein extraction yield. Although most are removed or reduced during alkaline solubilization and isoelectric precipitation processes, some remain in the resulting protein isolates. Selection of appropriate legume genotypes and different emerging and sustainable facilitating technologies, such as high‐power ultrasound, pulsed electric fields, high hydrostatic pressure, microwave, and supercritical fluids, can be applied to increase the removal of unwanted compounds. Some technologies can be used to increase protein yield. The technologies can also modify protein structure to improve digestibility, reduce allergenicity, and tune technological properties. This review summarizes recent findings regarding the use of emerging technologies to obtain high‐purity protein isolates and the effects on techno‐functional properties and health.